Rapid testing for respiratory syncytial virus in a resource-limited paediatric intensive care setting - Howard Newman; Donald Tshabalala; Sikhumbuzo Mabunda; Nokwazi Nkosi; Candice Carelson (African Journal of Laboratory Medicine, 2020)
We analysed the performance characteristics of the respiratory syncytial virus lateral flow rapid antigen assay in use when compared to a multiplex polymerase chain reaction for detection of respiratory viruses. The study was conducted at a tertiary paediatric hospital in Port Elizabeth, South Africa, from 01 January 2017 to 31 December 2018. We found the clinical sensitivity (36.8%) of the rapid test to be too low for routine diagnostic use. Knowledge of assay performance characteristics of rapid tests are important for appropriate interpretation of rapid test results.